(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to find out whether the Quizwhizzer application has an influence on the learning outcomes of class VII students in the Informatics subject. This research is quantitative with experimental methods. The research design is Pre-Experiment One Group Pretest-Posttest Control Group Design. The population used was class VII C students, totaling 17 boys and 16 girls. Data collection uses observation, questionnaires, and test questions. Data were analyzed using normality test, t test, validity test and reliability test. There are differences in student learning outcomes, this can be seen from hypothesis testing using the t-test. The results obtained by calculating the hypothesis test (t-test) mean the increase in posttest results was 72.12, while the increase in pretest results was 62.42, resulting in an increase in the result scores. posttest learning was 9.7 greater than pretest learning results. The value of Tcount > Ttabel (7.649 > 2.042) and the significance value is more than 0.05 (p=0.0000 < 0.05), it can be stated that there is a difference in increasing the value of learning outcomes in class VII C. Thus, it can be concluded that H0 is rejected, and Ha accepted